Is Iceland underlain by a plume in the lower mantle? Seismology and helium isotopes - Foulger, G. R.; Pearson, D. G. (Geophysical Journal International, 2001)
Tomographic images reveal an apparent fundamental disagreement in the interpretations of seismic data pertaining to the depth of the source of lavas erupted in the Iceland region and the assumptions in helium geochemistry modelling. Four recent independent tomography experiments image a major, strong, low wave speed anomaly in the upper mantle beneath Iceland that does not continue down into the lower mantle, confirming earlier studies. On the other hand, some 3He/4He ratios measured in volcanic rocks from the Iceland region are amongst the highest on Earth. Elevated 3He/4He ratios are conventionally viewed as resulting from excess 3He from a little degassed, primitive reservoir, often assumed to be in the lower mantle, and a high 3He/4He ratio is regarded as the most powerful geochemical indicator of a lower mantle plume. Suggested explanations for this disagreement include a model whereby material is transported up from the lower mantle by a structure that is too small to be detected by seismic tomography, and a model whereby high 3He/4He ratios arise from the upper mantle. These results have significant implications for models of plumes elsewhere.